The bias of the ECB inflation projections: A State-dependent analysis - Eleonora Granziera; Pirkka Jalasjoki; Maritta Paloviita (Bank of Finland, 2024)
We test for state-dependent bias in the European Central Bank's inflation projections. We show that the ECB tends to underpredict when the observed inflation rate at the time of forecasting is higher than an estimated threshold of 1.8%. The bias is most pronounced at intermediate forecasting horizons. This suggests that inflation is projected to revert towards the target too quickly. These results cannot be fully explained by the persistence embedded in the forecasting models nor by errors in the exogenous assumptions on interest rates, exchange rates or oil prices. The state-dependent bias may be consistent with the aim of managing inflation expectations, as published forecasts play a central role in the ECB's monetary policy communication strategy.
urn:nbn:fi-fe2024052234437
Keywords: C12; C22; C53; E31; E52; 330; Inflation Forecasts; Forecast Evaluation; ECB; Central Bank Communication